The Future of Internationalization of Higher Education in Europe - de Wit, Hans; Hunter, Fiona (International Higher Education, 2015)
A study has been made for the European Parliament on the understanding of internationalization of higher education (IoHE) in the European context, based on two surveys, an analysis of the role of digital learning, ten national reports from Europe and seven from outside Europe. The study results in conclusions and recommendations on the future of internationalization of higher education in Europe, based on the national reports and a Delphi process among experts in international higher education. This is a summary of the key findings of the study, including a redefinition of the meaning of internationalization.